Tendencies of legal regulation of scientific and scientific and technical activity in the Russian Federation and the Republic of Belarus - Andrichenko, Lyudmila V.; Plyugina, Inna V.; Gaunova, Zhanna A.; Maslovskaya, Tatiana S. (Journal of the Belarusian State University. Law, 2020)
The article highlights and explores the general trends of legal regulation of scientific and technical activities that are typical for the Russian Federation and the Republic of Belarus. There are a number of existing problems of legal regulation in this area, including insufficient legal regulation, lack of legal regulation, unification of the terms and notions, specification of the organizational structure of public administration in the sphere of science, scientific-technical and innovation activities and the transfer of research results into production, etc. The authors conclude that necessity of modernization of the legislation in the sphere of scientific, scientific-technical and innovation activities is required.